75 : {30 - [ 24 x ( 20 - 12 : a x 3 )] : 12+ 7} + 3=8
75 : {30 - [ 24 x ( 20 - 12 : a x 3 )] : 12+ 7} = 8 - 3 = 5
30 - [ 24 x ( 20 - 12 : a x 3 )] : 12+ 7 = 75 : 5 = 15
30 - [ 24 x ( 20 - 12 : a x 3 )] : 12 = 15 - 7 = 8
[24 x ( 20 - 12 : a x 3 )] : 12 = = 30 - 8 = 22
24 x ( 20 - 12 : a x 3 ) = 22 × 12
24 x ( 20 - 12 : a x 3 ) = 264
20 - 12 : a x 3 = 264 : 24
20 - 12 : a x 3 = 11
12 : a x 3 = 20 - 11
12 : a x 3 = 9
12 : a = 9 : 3
12 : a = 3
a = 12 : 3
a = 4 → numarul aflat prin metoda mersului invers